Factors influencing small handicraft enterprises to adopt technological innovation : Insights from Pakistani handicraft enterprises - Shafi, Mohsin; Zoya, ,; Muhammad Ashraf, Fauzi; Yang, Yongzhong (Routledge, 2024)
Technological innovation is crucial for enhancing the efficiency and competitiveness of small enterprises. However, the factors influencing its adoption in handicraft enterprises remain unknown. Therefore, this study explores the factors influencing small handicraft enterprises to adopt technological innovation and their impact on overall firm performance using data from 344 Pakistani small handicraft enterprises. Structural equation modelling was used for the data analysis. The results reveal that various factors such as artistic vision, resource constraints, and competition, among others, significantly and positively influence handicraft producers’ adoption of technological innovation. Furthermore, five distinct sources of innovation were identified as having a substantial influence on technological innovation. The findings also demonstrate that technological innovation significantly and positively affects the economic and cultural performance of enterprises. This study deepens our understanding of the different influencing factors and sources driving technological innovation in handicraft enterprises, suggesting that beyond customers’ needs or demands, many factors play crucial roles in influencing artisans to embrace technological innovation. In contrast to previous studies that reported customers, suppliers, or competitors as innovation sources, this study contributes to the literature by examining other sources, such as self-creativity and other artisans within the firm. Our findings have implications for theory and policy.